2023
DOI: 10.1161/atvbaha.123.318978
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Platelet mTORC2/Akt Pathway by Anti-β2GP1 Antibody Promotes Thrombosis in Antiphospholipid Syndrome

Abstract: BACKGROUND: Anti-β2GP1 (β2-glycoprotein 1) antibodies are the primary pathogenic antibody to promote thrombosis in antiphospholipid syndrome (APS), yet the underlying mechanism remains obscure. We aimed to explore the intracellular pathway that mediated platelet activation. METHODS: Platelets were isolated from patients with APS and subjected to RNA sequencing. Platelet aggregation, the release of platelet granules, platelet spreading, and clot retracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…The involvement of Akt signaling in ASO has also been demonstrated, as microRNA-21 was found to be upregulated in the arteries of ASO injury rat models, and was shown to regulate the function of VSMCs through the Akt and ERK1/2 pathways ( 30 ). Previous studies have also revealed that Akt signaling contributes to the triggering of platelet activation and thrombosis ( 31 , 32 ). The investigation of strategies to block Akt signaling may provide a solution to arterial occlusion.…”
Section: Discussionmentioning
confidence: 95%
“…The involvement of Akt signaling in ASO has also been demonstrated, as microRNA-21 was found to be upregulated in the arteries of ASO injury rat models, and was shown to regulate the function of VSMCs through the Akt and ERK1/2 pathways ( 30 ). Previous studies have also revealed that Akt signaling contributes to the triggering of platelet activation and thrombosis ( 31 , 32 ). The investigation of strategies to block Akt signaling may provide a solution to arterial occlusion.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, aPLs can activate complement through classical pathways, directly mediating platelet destruction [ 17 , 18 ]. Furthermore, in addition to activating the traditional p38/MAPK (mitogen activated protein kinase, MAPK) signaling pathway [ 19 ], recent research has shown that aPLs may also overactivate the mTORC2 (mammalian target of the rapamycin complex 2)/Akt pathway, inducing platelet activation and decreasing platelet count [ 20 ]. Our study corroborates the clinical medical perspective on the association between aPLs and SLE-TP.…”
Section: Discussionmentioning
confidence: 99%
“…Precise interventions aimed at signaling events directly involved in the pathological process as described 1,2 are promising techniques that may assure effective intervention without destabilizing the hemostatic cascade.…”
Section: See Accompanying Articles On Pages 1808 and 1818mentioning
confidence: 99%
“…Tamam Bakchoul, Nina Wolska I n this issue of Arteriosclerosis, Thrombosis, and Vascular Biology, 2 groups reported on novel signaling pathways upregulated by antibodies directed at platelets in immune thrombotic thrombocytopenia (ITT). Renna et al 1 present an article entitled "Novel strategy to combat the procoagulant phenotype in heparin-induced thrombocytopenia using 12-LOX inhibition" and the article "Activation of platelet mTORC2/Akt pathway by anti-β2GP1 antibody promotes thrombosis in antiphospholipid syndrome" is offered by Tang et al 2 Both works elegantly demonstrate that specific inhibition of platelet activation under pathophysiological conditions can effectively prevent thromboembolic events, probably without increasing the risk for thrombocytopenia-associated bleeding.…”
Section: Cooling Platelets Down In Antibody-mediated Immunothrombosismentioning
confidence: 99%